Reconstruction of a county-level resolution typhoon disaster database from 1980 to 2018 for China’s coastal area - Wu, Caiming; Ren, Fumin; Zhu, Jing; Chen, Peiyan; Lu, Yi (Frontiers in Earth Science, 2023)
This study develops a reconstructed a typhoon disaster database over a longer period 1980-2018 and at higher spatial resolution by using the current relatively complete county-level resolution disaster records for the eight coastal provinces of China from the shorter period 2004 to 2013. Typhoon precipitation and wind data over the shorter period are matched to disaster data and a functional relationship is derived between typhoon meteorological impact and typhoon disaster (direct economic loss). This relationship is used to construct a disaster data set for the longer period. The basic characteristics of the reconstructed database are documented and analyzed. The primary result of the paper is the production of the reconstructed dataset that can be made available to typhoon risk and disaster mechanism researchers. The second result is the development of the methodology for reconstruction, involving three main phases: disaster data expansion for individual stations, establishment of relationships between disaster and typhoon precipitation and wind, and disaster database reconstruction. The distributions of average annual accumulative damage and average annual frequency of disaster events in the reconstructed database correlate highly with that in disaster records. Based on reconstructed damage at the 10, 30, 70 and 97 percentile levels, the individual station-based (or typhoon case-based) disasters have been classified into five categories: mild, medium, large, severe and extremely severe. Finally, the annual cumulative damage shows a slight downward trend over time. Typhoon damage mainly occurs between July and September each year. For different category typhoons, the more severe damage the higher the proportion of typhoons that make landfall, the stronger the average maximum intensity during typhoon impact period and the longer the impact time. Typhoons that move northwestward before turning and moving northward and making landfall in eastern China cause more severe damage than those move westward and make landfall in southern China. In general, the reconstructed disaster database is meaningful and has value in practical applications. It also provides a data base for disaster assessment work.